AODV-based technique for quick and secure local recovery from link failures in MANETs. (1st January 2013) - Sarkar, Sajal; Datta, Raja
Wireless links in MANET may be broken frequently due to nodal mobility and power failures. Such problems make routing protocols, like AODV, inefficient and unreliable. Presently, these problems are solved using local repairing mechanisms at an intermediate node by creating an alternative route to the destination. But it increases routing overhead and unnecessarily consumes MANET resources. Further, if there are no checks on the selection of nodes while creating an alternative route, there is every possibility that a malicious node may take its place in the path. In this paper, we propose a technique which does a quick local recovery from the link failures and also avoids misbehaving nodes to creep in the path. The combined technique improves performances and also consumes less energy of nodes in MANET. Performance analysis and simulation results show that our proposed technique achieves significant performance improvement over existing AODV-based techniques.